THE INFLUENCE OF DISTRIBUTIONS EXPENSES AT RETURNING RATE FROM INVESTMENT IN THE OPEN INVESTMENT FOUNDS (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article focuses on problems connected with handling expenses beard by the investor. The paper also characterizes the factors which influence the height of distribu-tion expenses and presents their impact on returning rate from investment in the Open Investment Founds
Keywords: Investment Founds, distributions expenses, distribution charges, invest-ments risk, returning rate